2006
DOI: 10.1111/j.1365-2265.2006.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the aromatase inhibitor letrozole during adolescence increases near‐final height in boys with constitutional delay of puberty

Abstract: Our findings indicate that in adolescent boys an increase in adult height can be attained by use of aromatase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 24 publications
(32 reference statements)
1
59
2
1
Order By: Relevance
“…This realisation prompted the development of a novel treatment for boys with short stature using aromatase inhibitors, which block oestrogen production in order to prolong the duration of growth and to increase final height. Beneficial effects of aromatase inhibitors on growth have been reported in boys with constitutional delay of puberty and growth, idiopathic short stature and GH deficiency (Wickman et al 2001, Mauras et al 2004, Hero et al 2005, 2006b). The ease of administration, low cost and lack of overt toxicity of aromatase inhibitors make them a potential attractive strategy for treatment of boys with idiopathic short stature.…”
Section: Introductionmentioning
confidence: 99%
“…This realisation prompted the development of a novel treatment for boys with short stature using aromatase inhibitors, which block oestrogen production in order to prolong the duration of growth and to increase final height. Beneficial effects of aromatase inhibitors on growth have been reported in boys with constitutional delay of puberty and growth, idiopathic short stature and GH deficiency (Wickman et al 2001, Mauras et al 2004, Hero et al 2005, 2006b). The ease of administration, low cost and lack of overt toxicity of aromatase inhibitors make them a potential attractive strategy for treatment of boys with idiopathic short stature.…”
Section: Introductionmentioning
confidence: 99%
“…The delay in the tempo of bone age acceleration caused by aromatase inhibition and decreased estrogen resulted in treated with AI for twelve months, in combination with low dose testosterone therapy for 6 months [6]. The same subjects were followed until near final height [7] and the boys treated with AI attained a mean NAH 6.7 cm higher compared to the control group. Subsequent studies were done in patients with ISS and GHD [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The identification of one male with a point mutation in the estrogen receptor gene [3] and another male with a point mutation in the aromatase enzyme gene [4,5] confirmed that estrogen is the principal hormone causing epiphyseal closure. Studies involving AI in male patients with constitutional delay of growth and puberty [6,7], ISS [8,9], and GHD [10] suggest that AI can delay bone age acceleration and increase predicted adult height (PAH). However, data regarding adult height outcomes are limited [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Normal pubertal progression and bone health were found after 2 -3 years with this combination therapy (11) . Another randomized, placebo-controlled study could show that boys with constitutional delay of puberty who received the AI letrozole in combination with low-dose testosterone reached a higher mean near-fi nal height than boys on testosterone monotherapy (12) . Considering the positive effects of GH on BMD, the use of GH, together with an AI, might also be a treatment option in adolescents with ISS.…”
Section: Discussionmentioning
confidence: 99%